Shortcomings of services for persons with severe and persistent mental health challenges: a qualitative study of service users and family carers - Isaacs, Anton; Lambert, Caroline; Lawn, Sharon; Dyer, Anna (Frontiers in Psychiatry, 2024)
This study aims to explore the views and experiences of service users and carers on the services they have used for their mental health challenges and their suggestions for service reform.Twenty participants (15 carers and 5 service users) were interviewed for the study. Eight categories emerged from the data. They were: Several gaps in the system, Barriers to accessing services, Services are not fit for purpose, Services operate in isolation, System is not person focused, Service users and carers are treated poorly, Services are overloaded and under resourced and Recommendations for service reform. Respondents reported that a persistent lack of funding and resources for mental health services was a main cause of these shortcomings. Respondents also noted that innovations were needed to re-orient services to enable continuity of care, and training of mental health professionals was needed for a better understanding of the needs of service users and their carers. Additional research is needed with larger and more diverse samples to further explore these findings.